Perancangan Sistem Informasi Sanggar Seni Kirana Budaya Berbasis Website Menggunakan Metode Agile Development - Ayu Pramesti Maharani; Tito Prabowo; Fatra Nonggala Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Kirana Budaya Art Studio is an institution engaged in the preservation of arts and culture through various activities such as dance training and costume rental. However, the manual administration management causes various challenges, such as time efficiency, data accuracy, and limitations in conveying information to the wider community. To overcome these problems, a website-based information system was developed that was designed to support the studio's operational needs. This system was built using the Agile Development method, which allows the development process to be carried out iteratively by involving input from end users on an ongoing basis. This approach ensures that the resulting system can adapt to the dynamic needs of the studio. The main features developed include class registration, schedule management and activity classes, and costume rental. The purpose of this research is to produce a website-based information system using the Agile Development method that can disseminate information as well as become a medium for renting art products and services to the wider community in an easily accessible manner. The results of the implementation of this system show increased efficiency in data management, more effective delivery of information to users or customers, and optimization of promotions through digital media. With this website-based information system, the Kirana Budaya Art Studio can improve the quality of services and support efforts to preserve arts and culture in a more professional and modern manner.